Evolución del virus de hepatitis B : análisis de mecanismos involucrados en el establecimiento y progresión de la infección viral - Sevic, Ina (2017)
The hepatitis B virus (HBV), due to its quasispecies population structure, circulates as a collection of subpopulations of genetically related variants that evolve throughout the chronic infection. As a result of the evolutionary process, those viral subpopulations that have the greatest fitness for each particular situation during chronic infection are fixed.\nIn this work a new method was presented to evaluate the HBV viral fitness and it was used to evaluate the replicative fitness of HBV in two evolutionary scenarios: seroconversion process (intra-host) and occupation of the ecological niche (inter-host). This method facilitates the analysis of the interactions between different viral variants in a cotransfection process.\nIn this work it is concluded that:\nReplicative fitness is directly related to the replicative capacity of each variant analyzed.\nThe cotransfection with sgtD1del and sgtD1mut is the first evidence of the interaction between viral variants in the course of the replication of HBV in the same cellular system.\nThe greater replicative fitness of sgtF1b compared with sgtF4 makes a contribution to the understanding of the occupation of the ecological niche of new infections in Argentinaby the sgtF1b.